Live Commerce as a Digital Marketing Innovation for MSMEs: The Role of Interactivity and Consumer Trust in Enhancing Purchase Intention - Imam Jayanto; Wahyuni Sri Astutik (Technology and Society Perspectives (TACIT), 2026)
This study aims to analyze the role of live commerce as a digital marketing innovation for MSMEs by examining the influence of interactivity and consumer trust on purchase intention. The study employed a literature review method using a qualitative approach and descriptive analysis. Data were collected from Google Scholar, ScienceDirect, and relevant reports published by international organizations covering the period from 2010 to 2026. The initial search identified 50 publications, which were subsequently screened based on relevance, quality, and alignment with the research objectives, resulting in 41 articles selected for analysis. The findings indicate that interactivity serves as a key stimulus for increasing consumer engagement, while consumer trust reduces perceived risk and encourages purchase intention. The success of live commerce is influenced more by communication quality, information transparency, and seller credibility than by technological features alone. A limitation of this study is its reliance on secondary data; therefore, the findings depend on the quality of the reviewed literature and are not supported by direct empirical evidence. The findings are expected to enrich the digital marketing literature and provide practical insights for MSMEs in developing more adaptive marketing strategies.